If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + 5u = -27 Solving -2 + 5u = -27 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 5u = -27 + 2 Combine like terms: -2 + 2 = 0 0 + 5u = -27 + 2 5u = -27 + 2 Combine like terms: -27 + 2 = -25 5u = -25 Divide each side by '5'. u = -5 Simplifying u = -5
| (x+6)(3x-7)=0 | | -9u-29=2(u-9) | | x^2-3x+5=-x^2-7x+21 | | 4x^2-x=11x | | -7=-3+2x | | 2x+3(x-11)=7 | | 7x^2-6x-23=0 | | 7x^2-37x+10=0 | | x^2-16x-192=0 | | 2x^3+4x^2+96x=0 | | -22=-7w+5(w-2) | | 11n-2=6n-47 | | 4x-15=9x | | 5x^2-23+12=0 | | 4v+4=-12 | | 22y^2-47y+25=0 | | x+2(x-2)=4(x-4)+14 | | -4(u+7)=-6u-22 | | 2x-6-3+2(2x+8)=4x-1 | | 3x^2+8x+12=0 | | 12y^2+5y-3=0 | | 2=2x+8 | | -6x+4(x+2)=-8 | | 86-6(x-5)=29(x-1) | | 45-(2x+4)=2(x+3)+x | | 9(x-2)+5x-10x+3+6x+15=0 | | 5x+2(x+2)=2(x+12) | | 11x-5500=0 | | 0=2x^4-2x^2-40 | | 8x+46=3x+6 | | x+x+5=9 | | 3+4(3x+6)+3=5+2(2x+5)-3x |